2006
DOI: 10.1111/j.1365-2621.2005.tb08309.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Detection of Poultry in Cooked Meat Products

Abstract: JFS C: Food Chemistry and Toxicology een chicken or tur een chicken or turkey key key key key concentrations and ELISA signals permitted the quantification of poultry adulterants in cooked non-poultry meats. concentrations and ELISA signals permitted the quantification of poultry adulterants in cooked non-poultry meats. concentrations and ELISA signals permitted the quantification of poultry adulterants in cooked non-poultry meats. concentrations and ELISA signals permitted the quantification of poultry adulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Different products and consumption patterns require different adulteration identification techniques. At present, many approaches are established for meat authentication including biochemical methods, immunological methods, , molecular methods, and spectroscopic methods. The greatest progress in species identification over the last 25 years was achieved by using DNA-based methods such as the polymerase chain reaction (PCR). DNA shows much better stability and is generally universally applicable, as all tissue samples contain DNA .…”
Section: Introductionmentioning
confidence: 99%
“…Different products and consumption patterns require different adulteration identification techniques. At present, many approaches are established for meat authentication including biochemical methods, immunological methods, , molecular methods, and spectroscopic methods. The greatest progress in species identification over the last 25 years was achieved by using DNA-based methods such as the polymerase chain reaction (PCR). DNA shows much better stability and is generally universally applicable, as all tissue samples contain DNA .…”
Section: Introductionmentioning
confidence: 99%
“…A recent investigation found meat from undeclared species in 22.0% of analysed meat products (Ayaz, Ayaz, & Erol, 2006). Because of their abundance and lower price, chicken and turkey are commonly present and undeclared in ground beef and pork products (Djurdjevic, Sheu, & Hsieh, 2005), as well as in sausages and cold cut samples (Ghovvati, Nassiri, Mirhoseini, Heravi Moussavi, & Javadmanesh, 2009). Moreover, a survey conducted on 323 samples of doner kebabs in UK and published in January of 2009 found that 35.1% of the labels listed different meat species than that actually contained in the kebab (LACORS, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…The confirmation of halal status, an essential element of which is control over the absence of deliberately or accidentally added pork, is in demand among a significant number of consumers for religious reasons [10][11][12][13]. To replace declared expensive types of raw meat materials with cheaper alternatives, poultry products are generally used, primarily chicken meat, which is inexpensive [14][15][16]. Therefore, much attention has been paid to tools for controlling the pork and chicken adulteration of meat products, in terms of both practical monitoring and the development of new techniques.…”
Section: Introductionmentioning
confidence: 99%